Changes in nurses' views and practices concerning nurse prescribing between 2006 and 2012: results from two national surveys. (26th March 2014) - Kroezen, Marieke; de Veer, Anke; Francke, Anneke; Groenewegen, Peter; van Dijk, Liset
Abstract: Aims: To assess changes in the prescribing practices and views about nurse prescribing of Registered Nurses in the Netherlands between 2006 and 2012. Background: Considering the developments that took place in the Netherlands between 2006 and 2012, such as increased opportunities for nurse prescribing education and stricter control of nurses' prescribing practices, this study examines the extent to which nurses' prescribing practices and views have changed in the intervening years. In both years, nurses were not legally allowed to prescribe. Design: Survey study. Methods: Surveys were conducted in 2006 and 2012. Questionnaires were sent to a national sample of nurses. The questionnaires addressed nurses' views on nurse prescribing and the extent to which nurse prescribing took place in the respondents' work setting. Results: There were 386 and 644 respondents to the 2006 and 2012 surveys respectively. The proportion of nurses who said that they felt adequately equipped to prescribe medicines remained constant around 12%. Insufficient knowledge to prescribe remained the most important reason for feelings of inadequacy. More than a quarter of the nurses in both surveys stated that nurses in their team sometimes write prescriptions. There were few changes in views on the consequences of nurse prescribing for nurses' practice. Conclusion: Overall, nurses' support for nurse prescribing remained stable at a fairly cautious level, while the number of nurses feeling inadequately equipped to prescribe remained high. As nurse prescribing is expected to improve the quality and continuity of care, this should be taken into account in policy expectations.